Exercise Treatment for Sacroiliac Pain - Mooney, Vert; Pozos, Robert; Vleeming, Andry; Gulick, Jennifer; Swenski, David (Orthopedics (Thorofare, N.J.), 2001)
ABSTRACT The reciprocal relationship of the latissimus dorsi on one side and the gluteus maximus on the other side has been demonstrated anatomically. To demonstrate this relationship by muscle action, electromyographic studies were performed in 15 healthy individuals. This formed the baseline for evaluation of 5 symptomatic patients with sacroiliac dysfunction. Abnormal hyperactivity of the gluteus muscle on the involved side and increased activity of the latissimus on the contralateral side was contrasted with the normal function of the healthy individuals. All patients in the rotary strengthening exercise program improved in strength and return of myoelectric activity to more normal patterns.